A heat conducting medium and a hot rolling roller
By using nanoparticles and surfactant improved thermal conductivity media in hot rolls, the problem of low thermal conductivity efficiency of existing hot rolls is solved, achieving more efficient heat transfer and thermal conductivity improvement.
Patent Information
- Application Number
- CN202211141917.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-09-20
AI Technical Summary
The existing hot rolls have low thermal conductivity and poor thermal conductivity, mainly due to the low thermal conductivity of common thermal conductivity media such as water and thermal oil.
Using a thermal conductivity medium composed of water, nanoparticles and surfactants, nanoparticles such as nanosilicon dioxide and nanocopper increase the thermal conductivity. Surfactants reduce the surface energy of nanoparticles, promote their dispersion, and form an adsorption layer with high thermal conductivity. , the dispersion is enhanced by sonication.
The thermal conductivity coefficient and thermal efficiency of the thermal conductivity medium are significantly improved, the thermal conductivity of the hot rolls is solved, and more efficient heat transfer is achieved.
Smart Images

Figure BDA0003853956910000031 
Figure BDA0003853956910000041 
Figure BDA0003853956910000051
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of pressure rollers, and more specifically, to a heat-conducting medium and a hot rolling roller. Background Art
[0002] Rollers are the main working parts of rolling mills that cause continuous plastic deformation of metals, and hot rolling rolls are one of them. Heat-conducting medium is fed into the flow channel of the rolls, and the rolls are heated by heat exchange between the heat-conducting medium and the rolls to obtain hot rolling rolls.
[0003] Common heat transfer media include water, heat transfer oil, etc. The thermal conductivity of water is usually about 0.59W / (m·K), and the thermal conductivity of heat transfer oil is usually about 0.145W / (m·K). The thermal conductivity of the above heat transfer media is relatively low. Therefore, the heat transfer efficiency of the hot rolling roll made by using the above heat transfer media is low and the thermal conductivity performance is poor. Summary of the invention
[0004] In order to solve the problem of low heat conduction efficiency and poor heat conduction performance of hot rolling rollers, the present application provides a heat conduction medium and a hot rolling roller.
[0005] In the first aspect, the present application provides a heat-conducting medium adopting the following technical solution:
[0006] A heat-conducting medium is composed of the following raw materials in parts by weight: 58-78 parts of water; 0.1-0.5 parts of nanoparticles; and 0.13-0.6 parts of a surfactant, wherein the nanoparticles are one or more of nano-silicon dioxide, nano-cobalt, nano-copper, nano-copper oxide, nano-zinc oxide, nano-titanium dioxide, and carbon nanotubes.
[0007] By adopting the above technical solution, nanoparticles are prone to agglomeration in water. The addition of surfactants can reduce the surface energy of nanoparticles, increase the distance between nanoparticles, disperse them in water, reduce agglomeration, and form a uniform and stable system. On the one hand, the thermal conductivity of solid nanoparticles is much greater than that of liquid water. The addition of nanoparticles will enhance the heat transfer process inside the heat-conducting medium and improve the thermal conductivity of the heat-conducting medium; nanoparticles have a high specific surface area and a small particle size, are not easy to settle, and have a high frequency of interaction with water during movement, which can promote heat transfer between nanoparticles and water and improve the thermal conductivity of the heat-conducting medium; on the other hand, surfactant molecules are regularly arranged on the surface of nanoparticles to form an adsorption layer. The molecular arrangement of the adsorption layer is relatively regular, and the thermal conductivity of the adsorption layer is between water and nanoparticles. When heat is transferred between water and nanoparticles, the presence of the adsorption layer is conducive to reducing the interface thermal resistance between water and nanoparticles, which is conducive to heat transfer, thereby improving the thermal conductivity of the heat-conducting medium, solving the problem of low thermal conductivity efficiency and poor thermal conductivity of the hot rolling roller.
[0008] Preferably, the weight portion of the nanoparticles is 0.25-0.4 parts.
[0009] By adopting the above technical solution, when the weight portion of the nanoparticles is 0.25-0.4 parts, the content of the nanoparticles is moderate, agglomeration is not easy to occur, and the thermal conductivity of the heat-conducting medium can be greatly improved.
[0010] Preferably, the weight portion of the surfactant is 0.35-0.46 parts.
[0011] By adopting the above technical solution, when the weight portion of the surfactant is 0.35-0.46 parts, the content of the surfactant is moderate, the adsorption amount on the surface of the nanoparticles is moderate, and the dispersibility of the nanoparticles in water is good.
[0012] Preferably, the nanoparticles are nano-copper and / or nano-cobalt.
[0013] By adopting the above technical solution, when nano-copper and nano-cobalt are used together, there is a synergistic effect in improving the thermal conductivity of the heat-conducting medium, thereby improving the thermal conductivity efficiency of the heat-conducting medium.
[0014] Preferably, the surfactant is one or more of a triazine-containing surfactant, a pyridine-containing surfactant and an imidazoline-containing surfactant.
[0015] By adopting the above technical scheme, the above surfactants all contain nitrogen atoms that can provide lone pairs of electrons, which can coordinate with nano-copper and nano-cobalt, thereby enhancing the adsorption of the surfactant to the nano-copper and nano-cobalt, so that the surfactant is firmly wrapped on the surface of the nano-copper and nano-cobalt, improving the dispersibility of the nano-copper and nano-cobalt, and enhancing the stability of the thermal conductive medium; at the same time, it also makes the surfactant more regularly arranged on the surface of the nano-copper and nano-cobalt, thereby improving the thermal conductivity of the adsorption layer, and thus improving the thermal conductivity of the thermal conductive medium.
[0016] Preferably, the method for preparing the heat-conducting medium comprises the following steps:
[0017] The nanoparticles, surfactant and water are mixed, stirred and ultrasonically treated to obtain a heat conducting medium.
[0018] By adopting the above technical scheme, ultrasonic oscillation can weaken the interaction between nanoparticles, so that they are effectively dispersed, the dispersibility of nanoparticles is improved, and the stability of the heat-conducting medium is enhanced; under the action of surfactants, even after a long time, the ultrasonic effect is weakened, and the nanoparticles will not agglomerate and can still maintain good dispersibility in water.
[0019] Preferably, the ultrasonic treatment time is 1 h-3 h and the frequency is 40 kHz.
[0020] By adopting the above technical solution, when the ultrasonic treatment time is 1h-3h and the frequency is 40kHz, the ultrasonic time is moderate, which can effectively improve the dispersibility of the nanoparticles and enhance the stability of the heat-conducting medium.
[0021] In a second aspect, the present application provides a hot rolling roller, which adopts the following technical solution:
[0022] A hot rolling roller, wherein the heat conducting medium of the hot rolling roller is the aforementioned heat conducting medium.
[0023] By adopting the above technical solution, the thermal conductivity coefficient of the above heat-conducting medium is high and the thermal conductivity performance is good. The hot rolling roller made by using the above heat-conducting medium has high thermal conductivity efficiency and good thermal conductivity performance.
[0024] In summary, this application has the following beneficial properties:
[0025] 1. Since the present application adopts nanoparticles, water and surfactant to prepare the heat-conducting medium, on the one hand, the thermal conductivity of nanoparticles is much greater than that of water, and the addition of nanoparticles to water can improve the thermal conductivity of the heat-conducting medium, and the nanoparticles have a small particle size, a high frequency of collision with water, and good heat transfer performance with water; on the other hand, the addition of surfactants can not only improve the dispersibility of nanoparticles in water, but also can be regularly adsorbed on the surface of nanoparticles to form an adsorption layer with a thermal conductivity higher than that of water, reduce the interfacial thermal resistance between water and nanoparticles, facilitate heat transfer, and then improve the thermal conductivity of the heat-conducting medium, thereby solving the problems of low heat efficiency and poor thermal conductivity of the hot rolling roller;
[0026] 2. In the present application, nano-copper and / or nano-cobalt, as well as one or more of triazine-containing surfactants, pyridine-containing surfactants, and imidazoline-containing surfactants are preferably used. Since the above-mentioned surfactants all contain nitrogen atoms that can provide lone pairs of electrons, they can coordinate with nano-copper and nano-cobalt. On the one hand, they can enhance the stability of the thermal conductive medium system, and on the other hand, they can make the surfactants more regularly arranged on the surface of nano-copper and nano-cobalt, thereby improving the thermal conductivity of the adsorption layer and thus improving the thermal conductivity of the thermal conductive medium. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to the embodiments.
[0028] Unless otherwise specified, the specifications of the raw materials used in the following examples and comparative examples are shown in Table 1.
[0029] Table 1. Raw material specifications
[0030]
[0031] Preparation Example
[0032] Preparation example of surfactant
[0033] Preparation Example 1
[0034] Preparation of pyridine-containing surfactant: Add 1 g of 2-pyridinecarboxamide to 100 ml of DMF, mix well, heat to 50°C, slowly add 5 ml of dodecane bromide under light-proof conditions, terminate the reaction after 20 hours, filter, wash and dry to obtain the pyridine-containing surfactant.
[0035] Example
[0036] Example 1
[0037] A heat conducting medium, the formula of which is as follows:
[0038] Water 58g; Nano-silicon dioxide 0.1g; Sodium dodecylbenzene sulfonate 0.13g.
[0039] Preparation of heat-conducting medium: Nano-silicon dioxide and sodium dodecylbenzene sulfonate were added into water, mixed and stirred, and ultrasonically treated for 1 hour at a frequency of 40 kHz to obtain a heat-conducting medium.
[0040] Embodiment 2-5
[0041] A heat-conducting medium, which is different from Example 1 in that the raw material composition of the heat-conducting medium is different, and the specific composition is shown in Table 2 below:
[0042] Table 2. Raw material composition of heat transfer medium
[0043]
[0044] Example 6
[0045] A heat-conducting medium, which differs from Example 5 in that the mass of nano-silicon dioxide is replaced by nano-copper.
[0046] Example 7
[0047] A heat-conducting medium, which differs from Example 5 in that the mass of nano-silicon dioxide is replaced by nano-cobalt.
[0048] Example 8
[0049] A heat-conducting medium, which is different from Example 5 in that the selection of nanoparticles is different, and the nanoparticles are 0.18 g of nano-copper and 0.18 g of nano-cobalt.
[0050] Example 9
[0051] A heat-conducting medium, which differs from Example 8 in that the choice of surfactant is different, and the quality of sodium dodecylbenzene sulfonate is replaced by the pyridine-containing surfactant obtained in Preparation Example 1.
[0052] Example 10
[0053] A heat-conducting medium, which differs from Example 8 in that the choice of surfactant is different, and the quality of sodium dodecylbenzene sulfonate is replaced by a surfactant containing imidazoline.
[0054] Embodiment 11
[0055] A heat-conducting medium is different from Example 10 in that the preparation steps of the heat-conducting medium are different, nano-copper, nano-cobalt, an imidazoline-containing surfactant and water are mixed and stirred without ultrasonic treatment to obtain the heat-conducting medium.
[0056] Examples 12-13
[0057] A heat-conducting medium, which is different from Example 10 in that the ultrasonic treatment time is different, and the specific treatment time is shown in Table 3 below:
[0058] Table 3. Ultrasonication time
[0059] project Ultrasonic treatment time (h) Example 10 1 Example 12 3 Embodiment 13 2.5
[0060] Comparative Example
[0061] Comparative Example 1
[0062] A heat-conducting medium, which differs from Example 6 in that the mass of nano copper is replaced by micron copper.
[0063] Comparative Example 2
[0064] A heat-conducting medium, which differs from Example 7 in that the mass of nano-cobalt is replaced with micron-cobalt.
[0065] Comparative Example 3
[0066] A heat-conducting medium, which is different from Example 1 in that the raw material composition of the heat-conducting medium is different, and the surfactant (sodium dodecylbenzene sulfonate) is replaced with nano-silicon dioxide.
[0067] Application Examples and Comparative Examples
[0068] A method for preparing a hot rolling roller comprises the following steps:
[0069] Smelting, casting, rough machining, heat treatment, fine machining, injection of heat-conducting medium, sealing and molding, flaw detection, and obtaining hot rolling rollers.
[0070] The heat-conducting media are selected from Examples 1-13 and Comparative Examples 1-3, respectively, and their specific sources are shown in Table 4 below:
[0071] Table 4. Sources of heat transfer media
[0072]
[0073]
[0074] Performance testing
[0075] Detection Methods
[0076] The thermal conductivity of the heat-conducting medium prepared in Examples 1-13 and Comparative Examples 1-3 was tested using a thermal conductivity meter to characterize the thermal conductivity of the heat-conducting medium. The specific test results are shown in Table 5 below:
[0077] Test results
[0078] Table 5. Performance test of heat transfer medium
[0079]
[0080]
[0081] It can be seen from the data in Table 5 that the thermal conductivity of the heat-conducting medium prepared in the examples of the present application is good, and the thermal conductivity coefficients of Examples 1-13 are all ≥ 0.657 W / (m·K), among which Example 13 is the best example.
[0082] Combining Comparative Examples 1-2 and Examples 6-7 and Table 5, it can be seen that the thermal conductivity of Example 6, 0.701 W / (m·K), is much greater than 0.615 W / (m·K) of Comparative Example 1; the thermal conductivity of Example 7, 0.710 W / (m·K), is much greater than 0.617 W / (m·K) of Comparative Example 2. This may be because: Comparative Examples 1-2 use micron particles to replace nanoparticles, and the micron particles have a larger particle size and are easy to settle, and cannot achieve long-term dispersion stability, and the thermal conductivity of the obtained heat-conducting medium is low.
[0083] Combining Comparative Example 3 and Application Example 1 with Table 5, it can be seen that the thermal conductivity of Example 1 is 0.657 W / (m·K) which is much greater than 0.609 W / (m·K) of Comparative Example 3. This may be because: the addition of the surfactant in Example 1 can not only improve the dispersibility of the nanoparticles in water and reduce the possibility of agglomeration of nano-silicon dioxide in water; it can also be regularly adsorbed on the surface of nano-silicon dioxide to form an adsorption layer with a thermal conductivity higher than that of water, thereby reducing the interfacial thermal resistance between water and nano-silicon dioxide, facilitating heat transfer, and thereby improving the thermal conductivity of the heat-conducting medium.
[0084] It can be seen from Examples 1-5 and Table 5 that the thermal conductivity of Examples 1-2 is lower than that of Examples 3-5, which indicates that when the weight of the nanoparticles is 0.25-0.4 parts, the content of the nanoparticles is moderate, it is not easy to agglomerate, and the thermal conductivity of the heat-conducting medium can be greatly improved. When the weight of the surfactant is 0.35-0.46 parts, the content of the surfactant is moderate, the adsorption amount on the surface of the nanoparticles is moderate, and the dispersibility of the nanoparticles in water is good.
[0085] Combining Examples 6-8 and Table 6, it can be seen that the thermal conductivity of Example 8 is higher than that of Examples 6-7. The nanoparticles selected in Example 8 are 0.18 g of nano-copper and 0.18 g of nano-cobalt, which indicates that when nano-copper and nano-cobalt are used together, there is a synergistic effect in improving the thermal conductivity of the heat-conducting medium, thereby improving the thermal conductivity efficiency of the heat-conducting medium.
[0086] Combining Examples 8-10 and Table 5, it can be seen that the thermal conductivity of Examples 9-10 is higher than that of Example 8. The surfactants selected in Examples 9-10 are pyridine-containing surfactants and imidazoline-containing surfactants, respectively. This may be because: the above-mentioned surfactants all contain nitrogen atoms that can provide lone pairs of electrons, which can coordinate with nano-copper and nano-cobalt, enhance the adsorption of the surfactant to nano-copper and nano-cobalt, make the surfactant firmly wrapped on the surface of nano-copper and nano-cobalt, improve the dispersibility of nano-copper and nano-cobalt, and enhance the stability of the thermal conductive medium; at the same time, it also makes the surfactant more regularly arranged on the surface of nano-copper and nano-cobalt, improves the thermal conductivity of the adsorption layer, and thus improves the thermal conductivity of the thermal conductive medium.
[0087] Combining Examples 10-11 and Table 5, it can be seen that the thermal conductivity of Example 10 is higher than that of Example 11. This may be because Example 11 has not been ultrasonically treated. This shows that ultrasonic oscillation can weaken the interaction between nanoparticles, effectively disperse them, improve the dispersibility of nanoparticles, and enhance the stability of the thermal conductive medium. Under the action of surfactants, even after a long time, the ultrasonic effect weakens and the nanoparticles will not agglomerate, and they can still maintain good dispersibility in water.
[0088] Detection Methods
[0089] The hot rolling rollers prepared in Application Examples 1-13 and Comparative Examples 1-3 were respectively inserted into a constant temperature water bath, the water bath temperature was stabilized at 80°C, 5 temperature measurement points were taken from the axial direction of the hot rolling roller from bottom to top, and a group of temperature values (5 points) were measured every 10 seconds. When the measurement reached 180 seconds, the measurement was stopped. The thermal conductivity of the heat-conducting roller was characterized by the temperature difference at the 5 points. The specific test results are as follows:
[0090] Test results
[0091] In the first 10 seconds after being inserted into the water bath, the temperature of each temperature measuring point of Application Examples 1-13 rose sharply. When heated to 40 seconds, the temperature of each temperature measuring point began to stabilize, and the temperature difference of each temperature measuring point did not exceed 3° C. This shows that the hot rolling rollers prepared in Application Examples 1-13 have fast heat conduction speed and good temperature uniformity, good overall heat conduction performance, and high heat conduction efficiency.
[0092] When the hot rolling rollers prepared by using comparative examples 1-3 are heated to 40 seconds, the temperature difference of each temperature measuring point is still large, even exceeding 10°C; and when heated to 100 seconds, the temperature of each temperature measuring point tends to be stable. This shows that the heat conduction speed of the hot rolling rollers prepared by using comparative examples 1-3 is slow, and the temperature uniformity is poor, and the overall thermal conductivity is not good. This may be because comparative example 1-2 uses micron particles to replace nanoparticles, and the particle size of micron particles is large, easy to settle, and cannot form a uniform and stable system; while in comparative example 3, the surfactant (sodium dodecylbenzene sulfonate) is replaced by nano-silicon dioxide, and the nano-silicon dioxide agglomerates in water, has poor dispersibility, and there is no surfactant to form an adsorption layer on its surface. The interface thermal resistance between nano-silicon dioxide and water is large, resulting in a low thermal conductivity coefficient of comparative examples 1-3, poor thermal conductivity and poor temperature uniformity of comparative examples 1-3.
[0093] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A heat conducting medium, characterized in that: The invention is prepared by mixing 58-78 parts of water, 0.1-0.5 parts of nanoparticles and 0.13-0.6 parts of surfactant by weight, stirring and ultrasonic treatment; the nanoparticles are composed of nano copper and nano cobalt in a weight ratio of 1:1; and the surfactant is an imidazoline-containing surfactant.
2. The heat conducting medium according to claim 1, characterized in that: The weight portion of the nanoparticles is 0.25-0.4 parts.
3. The heat transfer medium according to claim 1, characterized in that: The weight portion of the surfactant is 0.35-0.46 parts.
4. The heat conducting medium according to claim 1, characterized in that: The method for preparing the heat-conducting medium comprises the following steps: mixing nanoparticles, a surfactant and water, stirring, and ultrasonically treating to obtain the heat-conducting medium.
5. The heat conducting medium according to claim 4, characterized in that: The ultrasonic treatment time is 1-3h and the frequency is 40kHz.
6. A hot rolling roller, characterized in that: The heat-conducting medium of the hot rolling roller is the heat-conducting medium described in any one of claims 1-5.
